Serological approaches for the diagnosis of schistosomiasis – A review. (February 2017) - Hinz, Rebecca; Schwarz, Norbert G.; Hahn, Andreas; Frickmann, Hagen
Abstract: Schistosomiasis is a common disease in endemic areas of Sub-Saharan Africa, South America and Asia. It is rare in Europe, mainly imported from endemic countries due to travelling or human migration. Available methods for the diagnosis of schistosomiasis comprise microscopic, molecular and serological approaches, with the latter detecting antigens or antibodies associated with Schistosoma spp. infection. The serological approach is a valuable screening tool in low-endemicity settings and for travel medicine, though the interpretation of any diagnostic results requires knowledge of test characteristics and a patient's history. Specific antibody detection by most currently used assays is only possible in a relatively late stage of infection and does not allow for the differentiation of acute from previous infections for therapeutic control or the discrimination between persisting infection and re-infection. Throughout the last decades, new target antigens have been identified, and assays with improved performance and suitability for use in the field have been developed. For numerous assays, large-scale studies are still required to reliably characterise assay characteristics alone and in association with other available methods for the diagnosis of schistosomiasis. Apart from S. mansoni, S. haematobium and S. japonicum, for which most available tests were developed, other species of Schistosoma that occur less frequently need to be taken into account. This narrative review describes and critically discusses the results of published studies on the evaluation of serological assays that detect antibodies against different Schistosoma species of humans. It provides insights into the diagnostic performance and an overview of available assays and their suitability for large-scale use or individual diagnosis, and thus sets the scene for serological diagnosis of schistosomiasis and the interpretation of results. Highlights: Narrative review on evaluated published serological assays for detection of antibodies against different Schistosoma spp. Overview on diagnostic performance and value, availability and suitability for large-scale use. Serological diagnosis is valuable for schistosomiasis control in low endemicity settings and for travel medicine. The establishment of a sensitive and specific gold standard could facilitate future evaluation studies.